FAKTOR FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR - TIKE KARTIKA (Jurnal Bisnis dan Akuntansi, 2012)
The objective of this research is to examine and obtain empirical evidence of the factors that influence auditor performance. There are 6 variable used in this study, the variables of audit structure, role conflict, organizational commitment, organizational behavior, good corporate governance, auditor’s independency as the independent variables and auditor performance as the dependent variable. This research is done at DKI Jakarta in 2011. The criteria of sample is the auditor must have graduated at least from bachelor degree and has experience as an auditor at least for two years. The population in this research is all auditors working at Public Accounting Firm in DKI Jakarta based on Directory List 2011 which is published by Institut Akuntan Publik Indonesia (IAPI). Data collected using questionnaires submitted directly to auditor are listed in Public Accounting Firm. Number of questionnaires distributed are 180 copies, and 147 copies have been returned, there are 110 copies of questionnaires can be used as the research sample. Purposive sampling method is used to obtain the samples. This research is uses multiple regression analysis as the data analysis method in this research. Based on hypothesis testing, it shows that there are three variables of independent in this research audit structure, role conflict, and organizational commitment affect auditor performance. On the other hand the organizational behavior, good corporate governance, and auditor’s independency do not affect to auditor performance.